Gross and Histo-Architectural Studies on the Vascular Tunic of Eyeball ofMurrah Buffalo (Bubalus bubalis) - Jyotirmay Adhikary; Partha Das; Rajesh Ranjan (Indian Journal of Veterinary Anatomy, 2025)
The present study was conducted to elucidate the gross and histological details of the vascular tunic of eyeball of Murrah buffalo as the vascular tunic plays an important role in providing nutrition to the eye as well as additionally providing a peculiar metallic luster to the eye in dark. 20 pairs of eyeball from adult Murrah buffaloes, irrespective of sex, were collected, examined grossly, dissected and preserved in 10% NBF for further histomorphological studies. The present study revealed that the choroid was a deeply pigmented dark brown tunic lying between the sclera and the retina. The ciliary body was the largest component of anterior uvea. Tapetum was found in the dorsal part of fundus of the choroid. The iris was pigmented, contractile diaphragm present between cornea and the lens.